PERSEPSI MASYARAKAT DESA TENTANG LEMBAGA KEUANGAN SYARIAH - Fita setiati (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
Abstract— The purpose of this study was to determine the perception of rural communities on the operations of Islamic financial institutions (IFI) in handling business financingfor the community in Sukopuro village, Jabung sub-district, Malang regency. This research use desciptive qualitative approach. The population used in this study were the Sukopuro villagers who were members of the Joint Business Group (JBG). Determination of the sample is done by purposive sampling with the criteria for the community that conducts business and utilizes funds from Islamic financial institutions in the area. The data collection techniques used are observation methods, interviews, documentation and focus discussion groups (FGD). Data analysis in the research in this study by recording data from the results of interviews, observation, documentation and FGD then organized to be sorted out to answer the problem formulation. This analysis is continued by finding and finding meaning related to the formulation of the problem. Keywords—: Perception of rural communities; Islamic Financial Institutions (LKS); Business Financing.